Evaluation of Neuroprotective Effect of Althaea Officinalis Flower Aqueous and Methanolic Extracts against H2O2-Induced Oxidative Stress in PC12 Cells: Protective activity of Althaea Officinalis against oxidative stress - Atefeh Arab; Rezvan Yazdianâ€Robati; Hasan Rezaei-Seresht; Melika Ehtesham-Gharaee; Fatemeh Soltani (Iranian Journal of Pharmaceutical Sciences, 2017)
This study was conducted to evaluate the possible antioxidant activity and neuroprotective effects of aqueous and methanolic extracts of Althaeaofficinalis flowers against H2O2-induced oxidative stress in PC12 cells. The antioxidant potential of extracts was evaluated by radical scavenging activity using 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. For cytoprotective activity, the cells were pretreated with different concentrations (12.5, 25, 50, 100, 200and 400 μg/ml) of the extracts for 24h and then incubated with H2O2(480 μM) for 3 h. In co-treatment protocol, cells were simultaneously treated with H2O2 (480 μM) and the same concentrations of extracts, used in pretreatment protocol. Percentage of viability was measured using MTT assay. The aqueous and methanolic extracts did not show strong DPPH radical scavenging activity (IC50 value of 128 and 255 μg/ml respectively) in comparison with ascorbic acid (IC50 value of 6.1 μg/ml). The cytoprtection study revealed that neither the methanolic, northe aqueous extractsat tested concentrations could protect the cells against H2O2-induced cytotoxicity compared to H2O2 alone, in either co-treatment or pre-treatment experiments. Despite reporting the antioxidant activity of A. officinalis L. flowers, it seems that such a negligible cytoprotective activity may be related to some other factors. On the other hand, the presence of moderate antioxidant activity does not guarantee the protective activity against oxidative stress.